Preparation and antimicrobial properties of LL-37 peptide immobilized lignin/caprolactone polymer film - OGAN, AYŞE; BİRBİR, MERAL; KAHRAMAN, MEMET VEZİR; GÜLSOY, NAGİHAN; MUTLU, ÖZAL; ÇAĞLAYAN, PINAR (WILEY, 2020)
The use of biopolymers has gained priority in tissue engineering and biotechnology, both as dressing material and for enhancing treatment efficiency. There is a demand for new biopolymers designed with protease inhibitors and antimicrobials. LL-37 is an important antimicrobial peptide in human skin and exhibits a broad spectrum of antimicrobial activity against bacteria, fungi, and viral pathogens. Using lignin which is an abundant carbohydrate polymer in nature and a polyacrylic acid, we prepared a lignin/caprolactone biodegradable film by plastifying caprolactone and polyacyrlic acid. Lignin/caprolactone biodegradable film was activated with CDI and then immobilized LL-37 peptide. The structure was elucidated in terms of its functional groups by attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR), and the morphology of the lignin/caprolactone biodegradable film was characterized by scanning electron microscopy (SEM) before and after the immobilization process. The amount of LL-37 immobilized was determined by ELISA method. It was found that 97% of LL-37 peptide was successfully immobilized onto the lignin/caprolactone biodegradable film. Antimicrobial activity was determined in the lignin/caprolactone biodegradable film samples by quantitative antimicrobial activity method. According to the results, LL-37 immobilized lignin/caprolactone biodegradable film samples were effective on test organisms; Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. In bio-compatibility assays, the ability to support tissue cell integration was detected by using 3 T3 mouse fibroblasts. Samples were examined under transverse microscope, non-immobilized sample showed a huge cellular death, whereas LL-37 immobilized lignin/caprolactone biodegradable film had identical cellular growth with the control group. This dual functional lignin/caprolactone biodegradable film with enhanced antibacterial properties and increased tissue cell compatibility may be used to design new materials for various types of biological applications.
Keywords: antimicrobial activities; biodegradable film; biopolymers; lignin; caprolactone; LL-37 peptide; LIGNIN; MEMBRANE; MECHANISM; COMPLEX